Psychometric Properties of the Communication Confidence Rating Scale for Aphasia (CCRSA): Phase 1. - Cherney, Leora R.; Babbitt, Edna M.; Semik, Patrick; Heinemann, Allen W. (Topics in Stroke Rehabilitation)
Confidence is a construct that has not been explored previously in aphasia research. We developed the Communication Confidence Rating Scale for Aphasia (CCRSA) to assess confidence in communicating in a variety of activities and evaluated its psychometric properties using rating scale (Rasch) analysis. The CCRSA was administered to 21 individuals with aphasia before and after participation in a computer-based language therapy study. Person reliability of the 8-item CCRSA was .77. The 5-category rating scale demonstrated monotonic increases in average measures from low to high ratings. However, one item ('I follow news, sports, stories on TV/movies') misfit the construct defined by the other items (mean square infit = 1.69, item-measure correlation = .41). Deleting this item improved reliability to .79; the 7 remaining items demonstrated excellent fit to the underlying construct, although there was a modest ceiling effect in this sample. Pre- to posttreatment changes on the 7-item CCRSA measure were statistically significant using a paired samples t test. Findings support the reliability and sensitivity of the CCRSA in assessing participants' self-report of communication confidence. Further evaluation of communication confidence is required with larger and more diverse simples.